The choice of high gradient magnetic separation processes for removal of Fe2O3 carriers from quartz raw material - Sekulic, Zivko; Bartulovic, Zoran; Mihajlovic, Slavica; Ignjatovic, Miroslav; Savic, Ljubinko; Jovanovic, Vladimir; Nisic, Dragana (Gospodarka surowcami mineralnymi, 2017)
This review article surveys the subject of choice of high gradient magnetic separation processes for removal of Fe carriers from quartz raw material by electromagnetic separator with magnetic field intensity of 1.4 T.